Discussion on the wrapping phenomenon of Cu-ZnO system by in-situ investigation during microwave sintering. (December 2022) - Cheng, Jie; Xiao, Yu; Wang, Yuanjie; Li, Yongcun; Hu, Xiaofang; Xu, Feng
Abstract: The microstructure evolution during zinc oxide (ZnO) and metallic copper (Cu) microwave sintering was in situ investigated by using synchrotron radiation computed tomography (SR-CT). Based on the SR-CT experiment, the coupling effect between the materials and the microwave electromagnetic field was discussed. During microwave sintering, special three-dimensional microstructure evolution was directly observed. The copper particles were gradually "wrapped" by surrounding zinc oxide particles. The special phenomenon of "wrapping" may be related to the change in the conductivity of semiconductor ZnO. It was proposed that there might be an "electromagnetic attraction" between particles during the "wrapping" process. The electromagnetic attraction was further discussed by comparing the microstructure evolution in different directions and at different initial distances. The center distance reduction of Cu-ZnO particles in the vertical cross section was more obvious, and the "wrapping" phenomenon was more obvious with a closer initial distance. The electromagnetic attraction proposed in this paper was supported by some experimental phenomena. The research in this article could have implications for revealing the mechanisms of microwave sintering. Graphical Abstract: ga1